2004
DOI: 10.1016/j.jasms.2004.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Using non-covalent complexes to direct the fragmentation of glycosidic bonds in the gas phase

Abstract: An investigation of the gas phase chemistry of proton bound oligosaccharide (S)-ligand (L) non-covalent complexes, [S ϩ H ϩ L] ϩ has been carried out using electrospray ionization (ESI) and tandem mass spectrometry in a quadrupole ion trap. When subjected to collision-inducedϩ complexes undergo a range of reactions that can be broadly classified into three main types: (1) Simple dissociation into the individual monomers; (2) cleavage of the oligosaccharide to form B-type sequence ions; (3) cleavage of the li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…Similar decomposition patterns have previously been reported for double-stranded DNA, which was shown to not dissociate into single-stranded DNA, but rather to lose a nucleobase. 23 Furthermore, it can be concluded that the dissociation pathway is the same as for free monobasic cytosinecontaining oligonucleotides, 24,25 but different from the dissociation of CMP and CTP, which dissociate from RNAse without breaking covalent bonds. This clearly suggests that cooperative non-covalent interactions can result in an interaction strength of a magnitude similar to that for covalent interactions.…”
Section: Multiple Binding Sites On Ribonuclease a By Nano-esi-ms 1015mentioning
confidence: 99%
“…Similar decomposition patterns have previously been reported for double-stranded DNA, which was shown to not dissociate into single-stranded DNA, but rather to lose a nucleobase. 23 Furthermore, it can be concluded that the dissociation pathway is the same as for free monobasic cytosinecontaining oligonucleotides, 24,25 but different from the dissociation of CMP and CTP, which dissociate from RNAse without breaking covalent bonds. This clearly suggests that cooperative non-covalent interactions can result in an interaction strength of a magnitude similar to that for covalent interactions.…”
Section: Multiple Binding Sites On Ribonuclease a By Nano-esi-ms 1015mentioning
confidence: 99%
“…For example, noncovalent complexes of phosphate anions of biological interest undergo condensation reactions including: diphosphate formation [2], triphosphate formation [3], and phosphorylation of peptides [4]. Noncovalent complexes between nucleobases and sugars promote the cleavage of saccharide bonds via condensation reactions [5]. Furthermore, a number of tetralkylammonium salts undergo gas-phase S N 2 reactions, including those involving organic counter ions (eq 1a) [6,7], inorganic counter ions (eq 2) [8], counter ions derived from biomolecules such as peptides (eq 3a, b) [9], DNA (eq 4a) [10], and glycerophosphocholine adducts (eq 5) [11].…”
mentioning
confidence: 99%
“…Although aromatics, but not carbohydrates, are efficiently protonated in solution, the highly abundant protonated saccharides and their fragments appear in the photofragment MS of the complexes (Figures B, B, and B). These observations suggest a proton and energy transfer from the aromatics to the saccharides in the electronic ground and/or, upon UV excitation, excited state of the complexes. Protonated aromatics are the most abundant photofragments observed for mono‐ (for example, d ‐/ l ‐glucose; Figure S5) and disaccharaides (Figure S6) that do not contain NAc groups.…”
Section: Figurementioning
confidence: 85%